Israel and the Cold War diplomacy, strategy and the policy of the periphery at the United Nations - Patten, Howard A (The library of international relations, 2013)
The book analyses the national interests and mutual concerns which shaped relations and strategy at the United Nations during the critical moments of the establishment of the State of Israel and the following forty years, before the ramifications of the Iranian Revolution became apparent.